2009
DOI: 10.1111/j.1939-1676.2008.0243.x
|View full text |Cite
|
Sign up to set email alerts
|

Survival Analysis of 97 Cats with Nasal Lymphoma: A Multi‐Institutional Retrospective Study (1986–2006)

Abstract: Background: Feline nasal lymphoma (NLSA) is a condition for which no standard of care exists. Hypothesis: There is no difference in survival times of cats with NLSA treated with single or multimodality therapy. Animals: Records from 97 cats diagnosed with NLSA were examined. Methods: The purpose of this retrospective study was to compare the survival times of cats with NLSA treated with radiation therapy (RT) alone, chemotherapy alone, or RT 1 chemotherapy and identify potential prognostic variables that affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
117
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(132 citation statements)
references
References 14 publications
7
117
7
Order By: Relevance
“…Thus, more advanced stages might have been potentially underestimated at diagnosis, leading to a false increase of the systemic spread rate later in course. However, our findings are comparable with other extranodal locations, like nasal lymphoma, where patients also develop distant tumour spread despite the initial local character of the disease …”
Section: Discussionsupporting
confidence: 87%
“…Thus, more advanced stages might have been potentially underestimated at diagnosis, leading to a false increase of the systemic spread rate later in course. However, our findings are comparable with other extranodal locations, like nasal lymphoma, where patients also develop distant tumour spread despite the initial local character of the disease …”
Section: Discussionsupporting
confidence: 87%
“…The use of chemotherapy drugs that are less likely to cause substantial GI toxicity, such as vinblastine, may help decrease the risk of chemotherapy‐associated weight loss during treatment, particularly in cats that are responding to treatment. Anemia at baseline was significantly negatively associated with LSS, which has been inconsistently reported previously for cats with lymphoma …”
Section: Discussioncontrasting
confidence: 62%
“…Previous studies have suggested that cats with nasal lymphoma respond well to chemotherapeutic treatment and have found no significant benefit of the addition of radiotherapy to the protocol (Polton and Brearley 2007, Haney and others 2009). The median survival time of this group (140 days) is comparable to several studies (Henderson and others 2003, Polton and Brearley 2007, Haney and others 2009), but less than other published reports ( Vail and others 1998, Teske and others 2002, Sfiligoi and others 2007), emphasising the need for further randomised studies to define the most appropriate treatment for this group of cats. In the current study, cats with nasal lymphoma achieving CR had the longest median survival of 749 days and thus every effort should be made to maximise the likelihood of achieving CR in this group of cats.…”
Section: Discussionmentioning
confidence: 99%